2011
DOI: 10.1002/jbm.a.33272
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and biodegradation of polycaprolactone‐sebacic acid blended gels

Abstract: Tissue engineering aims at creating biological body parts as an alternative for transplanting tissues and organs. A current new approach for such materials consists in injectable biodegradable polymers. Their major advantages are the ability to fill-in defects, easy incorporation of therapeutic agents or cells, and the possibility of minimal invasive surgical procedures. Polycaprolactone (PCL) is a promising biodegradable and elastic biomaterial, with the drawback of low-degradation kinetics in vivo. In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…The degradation of PCL is primarily caused by the hydrolytic cleavage of ester groups via surface erosion or bulk degradation pathways depending on diffusion-reaction phenomenon [39,40]. However, it was also shown that the degradation rate of materials varied and depended upon several factors including microstructure, macrostructure, molecular weight, environment and composition [21,41]. In this study, the faster degradation of ORC/PCL composites compared to the typical melt pressed PCL was a result of using highly absorbable ORC to rapidly produce large porous channels (50-800 microns) on composite layer side after its dissolution for ACSF to diffuse into the inner part of the composite and cause the bulk degradation to occur thoroughly.…”
Section: Discussionmentioning
confidence: 98%
“…The degradation of PCL is primarily caused by the hydrolytic cleavage of ester groups via surface erosion or bulk degradation pathways depending on diffusion-reaction phenomenon [39,40]. However, it was also shown that the degradation rate of materials varied and depended upon several factors including microstructure, macrostructure, molecular weight, environment and composition [21,41]. In this study, the faster degradation of ORC/PCL composites compared to the typical melt pressed PCL was a result of using highly absorbable ORC to rapidly produce large porous channels (50-800 microns) on composite layer side after its dissolution for ACSF to diffuse into the inner part of the composite and cause the bulk degradation to occur thoroughly.…”
Section: Discussionmentioning
confidence: 98%
“…PCL depolymerases are also responsible for the degradation of polylcaprolactone (synthetic polymer) found in bacteria (Nishida and Tokiwa 1993;Suyama et al 1998). Blended PCLs have a greater degradation rate when employed with 5% sebacic acid (Salgado et al 2011;Tokiwa et al 2009). Fungi are widely reported for the biodegradation of PCL and hydrolysis.…”
Section: Polylcaprolactonementioning
confidence: 99%
“…However, this degradation process can take up to 2 years, which is a significant drawback clinically (Middleton & Tipton 2000). Various modifications, such as the addition of sebacic acid, have been reported to improve its degradation rate (Salgado et al 2012). Similarly, PCL can be modified by cross-linking a functional group such as fumarate, resulting in the synthesis of polycaprolactone fumarate (PCLF) (Wang et al 2009;Salgado et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Various modifications, such as the addition of sebacic acid, have been reported to improve its degradation rate (Salgado et al 2012). Similarly, PCL can be modified by cross-linking a functional group such as fumarate, resulting in the synthesis of polycaprolactone fumarate (PCLF) (Wang et al 2009;Salgado et al 2012). However, this semi-crystalline product needs to be heated to a high temperature before it can be injected into any bone defect site.…”
Section: Introductionmentioning
confidence: 99%